Buletin UiTM Sarawak: Info Kampus Isu 60 Julai 2009 - Kipli, Nur Aida; Ramakrishnan, Prabha; Maniam, Yuthandy; Abdullah, Norazlin; Jack, Suriani; Abg Samah, Aizimah; Chiew, Fei Ha (Universiti Teknologi MARA, Sarawak, 2009)
I believe the latest designs and layout of this Info Kampus are simply fabulous. It is great that we can present new ideas and concepts in every edition. The reports on activities conducted by both the staff and students of UiTM Sarawak showed that we were actively involved in various activities organised within or outside our campus. We invite more news on events and activities conducted for the next publication. We welcome any comments from the readers to further improve our Info Kampus.